Review of New Perspectives on Academic Writing: The Thing That Wouldn’t Die - Livingstone, David (Journal of Academic Writing, 2023)
This review reflects on, 'New Perspectives on Academic Writing: The Thing That Wouldn’t Die', by Bernd Herzogenrath.